Knowledge is esssential for leaders-to-be- Tun Mahathir - UMP, PNC
More than 5,000 people comprising senior government officers, community leaders, industrial representatives, undergraduates, school students and local residents attended a national-level public lecture by prominent statesman and former prime minister Tun Dr. Mahathir Mohamad.